Acid‐Labile Amphiphilic PEO‐b‐PPO‐b‐PEO Copolymers: Degradable Poloxamer Analogs. Issue 9 (22nd March 2016) - Worm, Matthias; Kang, Biao; Dingels, Carsten; Wurm, Frederik R.; Frey, Holger
Abstract : Poly ((ethylene oxide)‐ b ‐(propylene oxide)‐ b ‐(ethylene oxide)) triblock copolymers commonly known as poloxamers or Pluronics constitute an important class of nonionic, biocompatible surfactants. Here, a method is reported to incorporate two acid‐labile acetal moieties in the backbone of poloxamers to generate acid‐cleavable nonionic surfactants. Poly(propylene oxide) is functionalized by means of an acetate‐protected vinyl ether to introduce acetal units. Three cleavable PEO‐PPO‐PEO triblock copolymers ( M n, total = 6600, 8000, 9150 g·mol −1 ; M n, PEO = 2200, 3600, 4750 g·mol −1 ) have been synthesized using anionic ring‐opening polymerization. The amphiphilic copolymers exhibit narrow molecular weight distributions ( Ð = 1.06–1.08). Surface tension measurements reveal surface‐active behavior in aqueous solution comparable to established noncleavable poloxamers. Complete hydrolysis of the labile junctions after acidic treatment is verified by size exclusion chromatography. The block copolymers have been employed as surfactants in a miniemulsion polymerization to generate polystyrene (PS) nanoparticles with mean diameters of ≈200 nm and narrow size distribution, as determined by dynamic light scattering and scanning electron microscopy. Acid‐triggered precipitation facilitates removal of surfactant fragments from the nanoparticles, which simplifies purification and enables nanoparticle precipitation "on demand." Abstract : A novel class of acid‐cleavable surfactants based on a PEO‐ b ‐PPO‐ b ‐PEO substructure with two acetal moieties at the block junctions is introduced in this work. The acid‐labile poloxamer analogs are employed as surfactants in miniemulsion polymerization (MEP) to fabricate well‐defined polystyrene nanoparticles. Susceptibility of the acetal junctions to acidic hydrolysis enables cleavage of the surfactant subsequent to the MEP, affording surfactant‐free nanoparticles.